Verena Böll - Denis Nosnitsin - Thomas Rave - Wolbert Smidt - Evgenia Sokolinskaia (eds.): Studia Aethiopica. In Honour of Siegbert Uhlig on the Occasion of his 65th Birthday - Crummey, Donald (Aethiopica, 2006)
Review